Use of audiovisual media and its impact on educational quality in the initial level of educational institution N ° 608 Puente Piedra - Lima - Peru - 2011 - Cordero Tocas, Lila Filomena (2018)
Scientific research we have done is basic, non-experimental causal correlational study factors are two: Using media and educational quality in the Initial Level of School No. 608 - Puente Piedra - Lima. The sample consisted of 24 teachers from the Initial Level of School No. 608 Stone Bridge . The research design is transactional , correlational , causal . bivariate cross . Using the media and the educational quality that properly : For two structured data collection and measurement and consists of two aspects questionnaires were prepared . The instruments meet the qualities of validity and reliability. The study raises the following hypothesis : The use of audiovisual media is significantly related to the quality of education in the Initial Level of School No. 608 - Puente Piedra - Lima.